Framing the question of attribution of extreme weather events - Otto, F; Allen, M; Stott, P; van Oldenborgh, G; Eden, J; Karoly, D (Nature Publishing Group, 2016)
Whenever an extreme weather or climate-related event occurs the extent to which human-induced climate change has played a role is routinely asked. Increasingly scientists are able to give robust quantitative answers to this question. Understanding how the overall risks of extreme events are changing in a warming world requires both a thermodynamic perspective and an understanding of changes in the atmospheric circulation.